THE ROLE OF ENGLISH AS FOREIGN LANGUAGE FLUENCY IN SHAPING LEARNERS’ POLITICAL VIEWS TOWARDS LIBERALISM - Alfa Ridzi; Fadlia; Purwati (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2024)
This study investigates the influence of English as a Foreign Language (EFL) fluency on learners’ political views, particularly towards liberalism. It explores the intersection of language learning, cultural perspectives, and political ideologies. The research focuses on fluent EFL learners expressing their political opinions on social media platforms, particularly on a TikTok post by @itsindahg, examining the connection between English fluency and the adoption of liberal ideology. The findings aim to contribute to our understanding of how language fluency may shape political beliefs and inform educational practices in EFL contexts. The methodology employed is rooted in a qualitative approach, analyzing the discourse of EFL learners to uncover patterns and themes that suggest a correlation between language fluency and political ideology. The findings suggest that learners with higher levels of English fluency demonstrate a greater propensity towards liberal views. This tendency is attributed to their enhanced ability to navigate and assimilate the cultural and ideological nuances embedded within the English language.